Discouraging Students Academic Dishonesty in Flipped Classroom - Dewati, Lucia Nino Widiasmoro (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2017)
Flipped Classroom presents teaching process at home through videos, handouts and listening passages before the class session. While in-class time is mostly devoted for questions and answers session, exercises, projects and discussion. The reason flipped classroom is needed for teachers in this era, simply because at the time students do the assignments inside the classroom, teachers would have the opportunities to observe students interaction, activities, improvement and even to solve students problem such as academic dishonesty. Thus, the question would be: to what extent is the urgency of implementing flipped classroom as one solution to discourage students academic dishonesty in writing classes? The study is conducted by employing Action Research. The findings confirm that performing Flipped Classroom is essential in order to discourage students academic dishonesty while assisting the teacher to observe students development in writing classes.